Endoscopic Endonasal Resection of Anterior Skull Base Meningiomas and Mucosa: Implications for Resection, Reconstruction, and Recurrence - Lee, John Y. K.; Barroeta, Julieta E.; Newman, Jason G.; Chiu, Alexander G.; Venneti, Sriram; Grady, M. Sean (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2013)
Background Meningiomas of the anterior skull base are attractive tumors for resection via an endoscopic endonasal route. The use of the vascularized Hadad-Bassagasteguy nasoseptal flap has dramatically reduced the cerebrospinal fluid (CSF) leak rate—the veritable Achilles heel of this surgical approach. Benign meningiomas, however, can erode through the nasal mucosa—the very same mucosa that is used to reconstruct the anterior cranial fossa floor. The goal of this study was to describe the presence of meningioma invasion into the mucosa in patients who underwent endoscopic endonasal resection of ventral skull base meningiomas. The implications of this finding are discussed with respect to resection, reconstruction, and recurrence.Patients, Materials, and Methods This is a retrospective review of three patients who underwent endoscopic endonasal complete resection of ventral skull base meningiomas. Surgically excised tissues were processed for routine histopathological analysis.Results A complete resection of the bone, dura, and tumor was performed in all three cases. Both patients with visual deficits improved. The first patient to undergo endoscopic surgical resection developed a CSF leak, but the later two patients with larger tumors did not. Histopathological analysis demonstrated mucosal invasion by World Health Organization (WHO) grade I meningioma in two of the three cases.Conclusion Ventral anterior skull base meningiomas can invade through bone into the mucosa. Because the endoscopic endonasal resection of these meningiomas often requires the use of a vascularized nasoseptal flap to minimize CSF leak complications, it is possible that the nasoseptal flap itself may be compromised by tumor tissue. The creation of the nasoseptal flap should take the findings of this study into consideration to minimize late recurrence.
Keywords: skull base; meningiomas; nasoseptal flap; mucosa; endoscopic